Design de serviço e atmosfera do ambiente: um estudo de caso em um supermercado gourmet em São Luís/MA - RODRIGUES, Rebeca Gomes Batista (2023)
The commercial landscape has expanded beyond the mere trading of goods and services, incorporating the experience as a fundamental part of the purchase process and employing multisensory stimuli to emotionally impact buyers. The atmosphere of the environment represents the initiative to design a space that generates specific emotional effects on the consumer, carefully considering all elements that compose the retail environment. This scenario is designed with the aim of positively influencing users, who are regarded as both the focal point of creation and co-creators, as their needs are the focus of the provided satisfactory experiences. The servicescape— where the service is delivered—is particularly relevant to the perception of value, being crucial to consider this space to enhance the experience of the intangible service provided. With this in mind, the present study emphasizes the Service Design approach to ensure the utility, usability, and desirability of service interfaces for users, while also effectively, efficiently, and distinctively meeting the needs of service providers. Therefore, the objective is to analyze how Service Design elements contribute to creating a positive shopping experience for users, especially in a retail gourmet supermarket. Through spatial assessments and the use of tools measuring consumers' visceral perception, this research aimed to formulate design recommendations with the intention of establishing a pleasant atmosphere for all visitors to the gourmet supermarket. The conclusions drawn from these analyses allowed for the identification that supermarket users evaluate the space based on the environment's atmosphere, and Service Design emerges as a means to address gaps in environmental improvement areas, striving not only for functional efficiency but also for the creation of a positive sensory experience for customers.